Infuence of speed and flow rate on road accidents: a case study along federal route 50 (FT 050) - Hor, Peay San (2013)
Federal Route 50 (FT 050) has an annual average daily traffic (AADT) of more than 68,000 vehicles daily at the Batu Pahat-Parit Raja stretch and above 22,000 vehicles daily at the Ayer Hitam-Parit Raja stretch in 2010. During peak hours, the traffic volume could even go beyond 9,000 veh/hr at certain sections. Works Ministry of Malaysia (KKR) reported that Federal Route 50 (FT 050) had been identified as the “deadliest stretch of road” in Malaysia. The road recorded more than an average of 1,000 accidents and 36 deaths annually since 2006. This research aims to study the effects of speed and flow rate on road accidents at selected sections along Federal Route 50 (FT 050), which each has different road characteristics. Spot speed study was carried out at KM 5, KM 10, KM 15, KM 20, KM 25 and KM 30 to evaluate the influence of speed upon road accidents, while traffic volume count was conducted at KM 5, KM 20 and KM 30 to identify the effect of flow rate upon road accidents. Besides that, site observation was also conducted at the selected sections, where road facilities and countermeasures were studied generally. A model produced using multiple regression analysis technique with backward method shows that road accident frequency increases with the increase of flow rate. The model estimates that every 200 pc/hr/lane increases accident frequency by about 9 acc/yr. On the other hand, speed relates to accident as an effect of flow rate. By categorising the sections of FT 050 into 3 different zones based on the frequency of road accidents, results reveal that road accidents frequency increases with speed at different rates.